2020
DOI: 10.7554/elife.56619
|View full text |Cite
|
Sign up to set email alerts
|

Experience, circuit dynamics, and forebrain recruitment in larval zebrafish prey capture

Abstract: Experience strongly influences behavior, but little is known about how experience is encoded in the brain, and how changes in neural activity are implemented at a network level to improve performance. Here we investigate how differences in experience impact brain circuitry and behavior in larval zebrafish prey capture. We find that experience of live prey compared to inert food increases capture success by boosting capture initiation. To explore the underlying neural basis, we studied the effects of prior expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 96 publications
1
40
1
Order By: Relevance
“…This could potentially place fish raised under naturalistic conditions at a disadvantage in our prey capture assay, since they have adapted to hunting in a richer visual environment than the reduced stimulation case. This would be potentially analogous to recent reports that whether zebrafish first experience dry or live food influences their subsequent behavior and brain development [64, 65].…”
Section: Discussionsupporting
confidence: 76%
“…This could potentially place fish raised under naturalistic conditions at a disadvantage in our prey capture assay, since they have adapted to hunting in a richer visual environment than the reduced stimulation case. This would be potentially analogous to recent reports that whether zebrafish first experience dry or live food influences their subsequent behavior and brain development [64, 65].…”
Section: Discussionsupporting
confidence: 76%
“…Heterozygous stxbp1b fish were generated by clustered regularly interspaced short palindromic repeats (CRISPR)-mediated knockout, as described ( Grone et al., 2016 ) and in-crossed with transgenic zebrafish expressing neuronal-specific GCaMP6f [ Tg (neurod1:GCaMP6f) line] ( Rupprecht et al., 2016 ). This unique transgenic neurod1 :GCaMPf line was developed for fast calcium imaging studies in larval zebrafish ( Oldfield et al., 2020 ). Pigment-free nacre ( mitfa -/- ) offspring with GCaMP6f expression were sorted on 4 days post fertilization (dpf) and used for calcium imaging experiments on 5-7 dpf.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, compared to controls, prey-experienced fish had higher visually-evoked neuronal activity in the telencephalon and the habenula, suggesting that the two brain structures may contain neurons regulating learning processes required for refining motor sequences involved in hunting behavior (Oldfield et al, 2020). In support of this hypothesis, the ablation of habenular neurons led to a reduction of capture efficiency (Oldfield et al, 2020). More work is needed to identify the precise forebrain circuits responsible for this form of learning.…”
Section: Modulation Of Exploratory and Foraging Behaviorsmentioning
confidence: 98%
“…In accord with these latter reports, it was shown that learning is involved in prey-capture behavior performed by young fish. Larvae exposed to live prey (paramecia or rotifers) displayed elevated capture success compared to naïve larvae or controls raised with inert food (Lagogiannis et al, 2020;Oldfield et al, 2020). Moreover, compared to controls, prey-experienced fish had higher visually-evoked neuronal activity in the telencephalon and the habenula, suggesting that the two brain structures may contain neurons regulating learning processes required for refining motor sequences involved in hunting behavior (Oldfield et al, 2020).…”
Section: Modulation Of Exploratory and Foraging Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation